New species of oribatid mites with auriculate pteromorphs (Acari, Oribatida, Galumnidae) from the Philippines - Ermilov, Sergey G.; Corpuz-Raros, Leonila (Zootaxa, 2015)
Three new species of oribatid mites of the family Galumnidae (Acari, Oribatida), Galumna (Cosmogalumna) vladopesici sp. nov., Carinogalumna philippinensis sp. nov. and Setogalumna luzonica sp. nov., are described from the Philippines. Galumna (Cosmogalumna) vladopesici sp. nov. is most similar morphologically to G. (C.) dongnaiensis Ermilov & Anichkin, 2013, but it differs from the latter by the surface of body, genital and anal plates, and by the number and size of notogastral porose areas. Carinogalumna philippinensis sp. nov. differs from all species of Carinogalumna by the number of notogastral porose areas and structure of lamellar and sublamellar lines. Setogalumna luzonica sp. nov. is most similar morphologically to S. excellens P. Balogh, 1985, but it differs from the latter by the body size, morphology of bothridial setae, anterior notogastral margin and notogastral porose areas Aa, and structure of lamellar and sublamellar lines. The genera Galumna and Carinogalumna are recorded for the first time in Philippines, and the genus Setogalumna in the Oriental region. Identification keys to known species of Galumna (Cosmogalumna) and Setogalumna are given.